Diseño de una planta de biogas como fuente de energía alternativa en la empresa APRODEMAG con el uso de suero lácteo. - Angulo Arias, Richard Flavio (2019)
The company APRODEMAG was founded in February 2008, It is located in the Cotopaxi Province, Latacunga Town, Mulaló Parish, Mácalo Grande Neighborhood. The company generates 34083 liters of lacto serum per month approximately, as a by-product of the cheese making process. These residues are stored in tanks of approximately 5000 liters, so that later it is moved by the people surrounding the company, which will serve as food for the pigs. Besides, the company has a monthly electricity consumption of 1733.11 kWh, which represents $ 155.98 each month, constituting 73% of cost, associated with the consumption of electricity in the cold room. Therefore, the main goal of this work is to design a plant for the treatment of Lacto Serum and the production of Biogas for the electrical energy generation to eliminate and / or reduce the previous problems in order to fulfill this objective, a plant was designed, which is formed, fundamentally, by a mixing tank, the biodigester, it has a built-in heat exchanger for heating the substrate up to the operating temperature. The total cost of the plant is $ 3003.58,it is the most expensive items, the 20,000-gallon tank that is used as a bio-digester or mixing tank. The daily production of biogas is estimated at approximately 97.84 m3 biogas / day with an energy content equivalent to 262 kW day, it would allow the company to meet 70% of the electricity needs.